Recent prison protests/ riots in South Africa reimagined with different outcomes: A conflict management perspective - Lӧtter, Casper; Bradshaw, Gavin (SA crime quarterly, 2024)
This article makes use of secondary data analysis to examine why conflicts in South African prisons, in the form of protest and/or riots, invariably end up in violence, resulting in the death or injury of prison officials and/or incarcerated people. Using the data on eight prison protests compiled by Lukas Muntingh, collected from a sociological/rights perspective, we re-examine these incidents from a conflict management perspective. The work of Burton and Galtung on peace studies is employed to reimagine the management of these case studies and we conclude that every one of these cases could conceivably have been stepping-stones to positive peace (a flourishing, trusting environment) rather than negative peace (mere desistance from violence) in our prisons. We conclude that investing funding in conflict management or transformation training by the Department of Correctional Services (DCS) is bound to generate meaningful benefits, including beyond prison walls. To allow an alternative dispute resolution regime to settle in DCS’s institutional culture, we recommend that the Emergency Support Team (EST) should only be employed as a very last resort, authorised by the Inspecting Judge for Correctional Services (or someone independent of DCS) after consultation with the Minister of Correctional Services.